GENERATIVE AI TOOLS AND EFL LEARNER INDEPENDENCE: ARE THEY BUILDING INDEPENDENT LEARNING OR DEPENDENCE ON TOOLS - Rynda Mayasari; Hadiyanto Hadiyanto; Nyimas Triyana Safitri (ACADEMIA: Jurnal Inovasi Riset Akademik, 2026)
ABSTRACT The rapid advancement of generative artificial intelligence (AI) has transformed academic writing practices in English as a Foreign Language (EFL), while simultaneously raising pedagogical concerns about whether AI strengthens learner independence or promotes cognitive dependency. Addressing this issue, the present study synthesises empirical evidence to explain how generative AI shapes these contrasting outcomes in EFL/ESL academic writing within the global higher education context. The study employed a Systematic Literature Review guided by the PRISMA 2020 reporting framework. The literature search covered six information sources and involved systematic identification, screening, eligibility assessment, and thematic synthesis of 34 open-access, peer-reviewed articles published between 2022 and 2025. The synthesis revealed that AI enhances writing self-efficacy, self-regulated learning, metacognitive awareness, and independent writing performance when used as a form of scaffolding that encourages reflection, critical evaluation, and active learner engagement throughout the writing process. Conversely, using AI to replace idea generation, decision-making, and revision may foster cognitive, behavioural, and emotional dependency by reducing learners' intellectual involvement in writing. The principal contribution of this review is the development of the scaffold-to-dependency framework, demonstrating that the educational impact of AI is shaped not by the technology itself but by pedagogical design, AI literacy, learners' critical engagement, and the regulation of AI use during learning. These findings provide a conceptual foundation for developing curricula, assessment practices, and institutional policies that integrate AI responsibly while sustaining the development of independent academic writing. ABSTRAK Perkembangan pesat generative artificial intelligence (AI) telah mengubah praktik penulisan akademik English as a Foreign Language (EFL), sekaligus memunculkan perdebatan mengenai perannya dalam memperkuat kemandirian belajar atau justru meningkatkan ketergantungan kognitif mahasiswa. Berangkat dari isu tersebut, penelitian ini mensintesis bukti empiris untuk menjelaskan bagaimana AI generatif membentuk kedua kecenderungan tersebut dalam penulisan akademik EFL/ESL pada konteks pendidikan tinggi global. Kajian dilakukan menggunakan desain Systematic Literature Review dengan mengacu pada pedoman PRISMA 2020. Penelusuran literatur dilakukan melalui enam sumber informasi, dilanjutkan dengan proses identifikasi, seleksi, penilaian kelayakan, dan sintesis tematik terhadap 34 artikel peer-reviewed berakses terbuka yang diterbitkan pada periode 2022–2025. Sintesis menunjukkan bahwa AI mampu memperkuat efikasi diri, regulasi diri, kesadaran metakognitif, serta kemampuan menulis mandiri ketika dimanfaatkan sebagai scaffolding yang mendorong refleksi, evaluasi kritis, dan keterlibatan aktif mahasiswa dalam proses menulis. Sebaliknya, penggunaan AI sebagai pengganti penyusunan gagasan, pengambilan keputusan, dan revisi berpotensi memunculkan ketergantungan kognitif, perilaku, dan emosional yang mengurangi keterlibatan intelektual penulis. Kontribusi utama penelitian ini terletak pada perumusan kerangka scaffold-to-dependency, yang menunjukkan bahwa dampak AI tidak ditentukan oleh teknologinya, melainkan oleh desain pedagogis, literasi AI, keterlibatan kritis mahasiswa, dan pengaturan penggunaan AI selama proses pembelajaran. Temuan ini memberikan dasar konseptual bagi pengembangan kurikulum, asesmen, dan kebijakan pendidikan tinggi yang mengintegrasikan AI secara bertanggung jawab sekaligus menjaga perkembangan kemampuan menulis akademik secara mandiri.